A aprendizagem de geometrias não Euclidianas : um estudo realizado com professores da rede pública de ensino - Carli, Francielli Aparecida Rocha de (2012)
In the end of 2006, the Government of Parana State included on the State's Curricular Guidelines (DCEs) a new mathematics content: Topics of Non-Euclidean Geometry. Projects developed by the State University of Maringa (UEM) and the Regional Education Centers (NRE) aimed to train teachers of Public Schools to understand and work with these contents in the classroom through Continuing Education Courses. Thinking about the uneasiness of University professors who taught these courses and toward the difficulties presented by the course participants and because some of these difficulties seemed to be recurrent in different classes, the author had the intention to search: "What are the difficulties presented by those teachers when they study the Non-Euclidean Geometries?" At first, it was considered that these difficulties permeate specific knowledge of non- euclidean geometries, however, during the analyzes - which were based on the ?Content analysis? theory proposed by Bardin (1977) - other difficulties related to Euclidean Geometry knowledge were detected. According to the information above, this paper presents the difficulties related to Euclidean and Non-Euclidean Geometry shown during a training course.